Correlation of ground motion parameters based on strong-motion records and GMPE residuals in western China - Xiufeng Tian; Nana Chang; Minglang Che; Xuan Zhang (Geosciences Journal, 2026)

Regulatory patterns and driving factors of soil aggregates on the environmental behavior of heavy metals: A global study based on meta-analysis and machine learning - Yu-Xuan Song; Yuhan Meng; Bingxuan Zhao; Tian-Hao Che; Zining Li; Zuozhou Yu; Xinyang Zhen; Yining Li; Chengyong Li; Quan-Ying Wang; Jing-Ya Zhou (Environmental Geochemistry and Health, 2026)

Long Hypocotyl 1 mediates nitrogen regulation of flowering time and nitrogen use efficiency - Xingliang Duan; Guanjie Wang; Qinglin Song; Jiale Liu; Huilin Ding; Jing Che; Wei Xuan (Plant Science, 2026)

Guest Editors’ Introduction - Warwick Gullett; Makoto Seta; Juei-Cheng Jao; Jason Chuah; Nguyen Thi Xuan Son; Yi-Che Shih; Hance Smith; Arie Afriansyah (Coastal Management, 2026)

Hydraulic characteristics of short-distance fishway and their influence on fish upstream migration behavior - Wei Yang; Liwei Tan; Xianbin Zhang; Xuan Che; Ziyue Zhu; Geng Li (Ecological Engineering, 2026)

Design and performance verification of crab seedling automatic counting equipment based on improved YOLOv11+DeepSORT - Changfeng Tian; Xuan Che; Lei Ge; Zhi Qu; Mengxia Han (Aquacultural Engineering, 2026)

Spatiotemporal evolution characteristics of extreme precipitation indices in the Yangtze river delta region during 1961–2022 - Dong Gao; Mingliang Che; Zihan Ma; Ting Huang; Jiyi Zhang; Yingli Wang; Yong Xuan (Theoretical and Applied Climatology, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Decoding adenomyosis pathogenesis using an assembloid model - Yiliang Xu; Tao Cheng; Jianzhang Wang; Zhiruo Qiu; Xiaohong Guan; Yayuan Yu; Jiacheng Shen; Fangfang Xu; Xiaohong Jiang; Dandan Bai; Mingzhu Wang; Shuyan Mei; et al. (Science China Life Sciences, 2026)

Research on Intelligent Development and Processing Technology of Crab Industry - Zhi Qu; Changfeng Tian; Xuan Che; Zhijing Xu; Jun Chen; Xiyu He (Fishes, 2025)
As an important component of the global fishery economy, the crab breeding and processing industry faces the dual challenges of sustainable development and technological upgrading. This paper first systematically analyzes the regional distribution and core biological characteristics of major global economic crab species, laying a foundation for the targeted design of processing technologies and equipment. Secondly, based on advances in crab processing technology, the industry is categorized into two systems: live crab processing and dead crab processing. Live crab processing has formed a full-chain technological system of “fishing–temporary rearing–depuration–grading–packaging”. Dead crab processing focuses on high-value utilization: high-pressure processing enhances the quality of crab meat; liquid nitrogen quick-freezing combined with modified atmosphere packaging extends shelf life; and biological fermentation and enzymatic hydrolysis facilitate the green extraction of chitin from crab shells. In terms of intelligent equipment application, sensor technology enables full coverage of aquaculture water quality monitoring, precise classification during processing, and vitality monitoring during transportation. Automation technology reduces labor costs, while fuzzy logic algorithms ensure the process stability of crab meat products. The integration of the Internet of Things (IoT) and big data analytics, combined with blockchain technology, enables full-link traceability of the “breeding–processing–transportation” chain. In the future, cross-domain technological integration and multi-equipment collaboration will be the key to promoting the sustainable development of the industry. Additionally, with the support of big data and artificial intelligence, precision management of breeding, processing, logistics, and other links will realize a more efficient and environmentally friendly crab industry model.

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Desorption of adsorbed lead(II) on hydrochar under conditions of soil pH and fluctuating redox potential induced by waterflooding - Yufan Che; Jianfeng Zhang; Xuan Chen; Xiaoqian Ding; Jie Wang; Lixiang Wang; Xiaoguang Meng (Journal of Environmental Chemical Engineering, 2025)

Development and multi-objective optimization of a solar-powered hybrid aerator for aquaculture - Zhi Qu; Changfeng Tian; Xuan Che; Mengxia Han; Yin Zhou (Aquacultural Engineering, 2025)

Impact of different culture substrates on the water environment and growth performance of Babylonia areolata in a recirculating aquaculture system - Jiahua Zhang; Jie Wang; Zhaojun Gu; Xuan Che; Xingguo Liu (Aquacultural Engineering, 2025)

Estimating the Permeability–Depth Relation of Slate Formation for Geothermal Project - Xuan-Xinh Nguyen; Che-Wei Yeh; Tan-Minh Le; Jia-Jyun Dong; Chih-Hsi Liu; Chi-Ping Pan (Rock Mechanics and Rock Engineering, 2025)

Impacts of Low-Order Stream Connectivity Restoration Projects on Aquatic Habitat and Fish Diversity - Xinfeng Li; Xuan Che; Xiaolong Chen; Changfeng Tian; Jiahua Zhang (Fishes, 2025)
River barriers constitute a key factor that is degrading river connectivity and represent a critical research focus in riverine ecosystem conservation. Management authorities and river restoration agencies globally have increasingly employed barrier removal or modification for connectivity restoration projects in recent years, practices that are widely discussed and empirically supported in academia. However, existing research predominantly focuses on large dams in primary rivers, overlooking the more severe fragmentation caused by low-head barriers within low-order streams. This study targets the Yanjing River (total length: 70 km), a third-order tributary of the Yangtze River basin, implementing culvert modification and complete removal measures, respectively, for two river barriers distributed within its terminal 9 km reach. Using differential analysis, principal component analysis (PCA), cluster analysis, Mantel tests, and structural equation modeling (SEM), we systematically examined the mechanisms by which connectivity restoration projects influences aquatic habitat and fish diversity, the evolution of reach heterogeneity, and intrinsic relationships between aquatic environmental factors and diversity metrics. Results indicate that (1) the post-restoration aquatic habitat significantly improved with marked increases in fish diversity metrics, where hydrochemical factors and species diversity exhibited the highest sensitivity to connectivity changes; (2) following restoration, the initially barrier-fragmented river segments (upstream, middle, downstream) exhibited significantly decreased differences in aquatic habitat and fish diversity, demonstrating progressive homogenization across reaches; (3) hydrological factors exerted stronger positive effects on fish diversity than hydrochemical factors did, particularly enhancing species diversity, with a significant positive synergistic effect observed between species diversity and functional diversity. These studies demonstrate that “culvert modification and barrier removal” represent effective project measures for promoting connectivity restoration in low-order streams and eliciting positive ecological effects, though they may reduce the spatial heterogeneity of short-reach rivers in the short term. It is noteworthy that connectivity restoration projects should prioritize the appropriate improvement of hydrological factors such as flow velocity, water depth, and water surface width.

Immobilization of Pb in Alkaline Soil Amend with Nano-hydroxyapatite: Speciation, Bioavailability, and Bioaccessibility - Kai Che; Jinxing Yu; Yukun Ju; Xuan Zhao; Yunqian Gong; Chongming Chen (Bulletin of Environmental Contamination and Toxicology, 2025)

Constructing sodium L-aspartate assisted N-doped carbon encapsulated hollow CoP spheres with enhanced electrochemical kinetics and its derived macroporous N-doped carbon foam for high-energy density hybrid supercapacitors - Xiaolin Liu; Tian Tian; Aifeng Liu; Zengcai Guo; Jingbo Mu; Xiaoliang Zhang; Xuan Yue; Xiaoyan Liu; Fei Gao; Hongwei Che (Chemical Engineering Journal, 2025)

Risks of respiratory and circulatory system diseases induced by exposure to PM2.5 in high humidity and low solar radiation environments: disease types, genes, and functions - Xiaomeng Li; Liru Zhang; Zhengliang Zhang; Xuan Li; Jingli Qian; Jiawei Zhou; Hanxiong Che; Yan Han; Xin Qi; Fumo Yang; Yu Huang; Chao Peng; et al. (Environmental Geochemistry and Health, 2025)

Development and evaluation of an electrical impedance tomography (EIT) sensor for real-time monitoring of hemolysis dynamics - Piao Peng; Yue Fu; Bo Che; Xuan Li; Lei Liu; Jing Sun; Teng Luo; Linhong Deng (Analytica Chimica Acta, 2025)

Numerical Simulation and Experimental Study of a Small-Scale Vacuum Fish Pump - Changfeng Tian; Zhi Qu; Xuan Che; Mengxia Han; Yin Zhou; Fan Wu (Journal of Marine Science and Engineering, 2024)
The existing vacuum fish pump is too large and difficult to move, which is difficult to apply to small fishing vessels. However, the development of a small vacuum fish pump is not a single scaling of the existing vacuum fish pump but requires the support of relevant experiments and simulation theories. In this study, a vacuum fish pump suitable for small fishing vessels was developed. Firstly, a numerical model of the internal flow field during the vacuum fish pump’s working process was established using computational fluid dynamics (CFDs) and verified its effectiveness by physical experiments. It is found that the VOF model can well predict the variation of the volume fraction of the liquid phase in the whole calculation area with time during the suction or drainage process of the vacuum fish pump. Then, the internal flow field characteristics of the fish pump under different working conditions were simulated, and the rationality of the design of the fish pump was evaluated according to the numerical results. Finally, a separate physical experiment was carried out on grass carp, carp, crucian carp, silver carp, and bighead carp, respectively, and the capture efficiency and corresponding fish damage rate for different fish were analyzed. The experimental and numerical results show that the vacuum suction fish pump can achieve efficient and automatic suction and transport of live fish.

Enlarged scars: The effects of economic policy uncertainty on electricity accessibility and urban-rural disparity - Congyu Zhao; Xuan Zhai; Miaomiao Tao; Shuai Che (Utilities Policy, 2024)

Comparison of environmental impacts from pyrolysis, gasification, and combustion of oily sludge - Hongdi Yu; Fawei Lin; Xuan Guo; Chujun Luan; Jiantao Li; Rundong Li; Lei Che; Wangyang Tian; Guanyi Chen (Journal of Hazardous Materials, 2024)

Lung cell injury risks of PM2.5 exposure in the high humidity and low solar radiation environment of southwestern China - Qin Zhang; Xuan Li; Xiaomeng Li; Ronghua Zhang; Bi Ren; Hanxiong Che; Xin Qi; Jiawei Zhou; Jiancai Tang; Andre S.H. Prevot; Zhenzhong Liu; Li Jiang; et al. (Atmospheric Environment, 2024)

Effects of filter-feeding fish faeces on microbial driving mechanism of lake sediment carbon transformation - Yiming Li; Xuan Che; Hongyuan Chen; Zhanpeng Meng; Xinfeng Li; Xiaodong Wang; Lin Zhu; Yunlong Zhao (Science of The Total Environment, 2024)

Transcriptomic analysis reveals nanoplastics-induced apoptosis, autophagy and immune response in Litopenaeus vannamei - Yiming Li; Yucong Ye; Xiaoyi Zhu; Xingguo Liu; Xinfeng Li; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Dietary lipid supplementation alleviated the impacts of polystyrene nanoplastic exposure in Litopenaeus vannamei - Yiming Li; Yucong Ye; Haojuan Yuan; Siwen Li; Na Rihan; Xingguo Liu; Yunlong Zhao; Xuan Che (Aquatic Toxicology, 2024)

Improvement of gram staining effect by ethanol pretreatment and quantization of staining image by unsupervised machine learning - Xuan Guo; Wenming Che (Archives of Microbiology, 2024)

Exposure to polystyrene nanoplastics induces apoptosis, autophagy, histopathological damage, and intestinal microbiota dysbiosis of the Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Haojuan Yuan; Na Rihan; Mingming Han; Xingguo Liu; Tian Zhu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Characterization of risks and pathogenesis of respiratory diseases caused by rural atmospheric PM2.5 - Ronghua Zhang; Xiaomeng Li; Xuan Li; Qin Zhang; Jiancai Tang; Zhenzhong Liu; Guiqin Song; Li Jiang; Fumo Yang; Jiawei Zhou; Hanxiong Che; Yan Han; et al. (Science of The Total Environment, 2024)

Multicomponent chitosan complex/polyvinyl alcohol blended film with full-band UV-shielding performance and excellent antioxidant property for active food packaging - Heng Chen; Xiao Duan; Xinru He; Wenfeng Che; Zhanpeng Zhang; Xuan Xuan; Liwei Wang; Biao Wang; Jianbin Xu; Xin Wang (Carbohydrate Polymers, 2024)

Polystyrene nanoplastics exposure alters muscle amino acid composition and nutritional quality of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

Polystyrene nanoplastics induce lipid metabolism disorder and alter fatty acid composition in the hepatopancreas of Pacific whiteleg shrimp (Litopenaeus vannamei) - Yiming Li; Yucong Ye; Na Rihan; Bihong Zhu; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2024)

A Numerical Simulation Study and Effectiveness Evaluation on the Flow Field Effect of Trapezoidal Artificial Reefs in Different Layouts - Xiaolong Chen; Xuan Che; Yin Zhou; Changfeng Tian; Xinfeng Li (Journal of Marine Science and Engineering, 2023)
The combined release of artificial reefs in different quantities and arrangements leads to different flow field effects. This study designs a small trapezoidal artificial reef. To optimize the quantity and layout of these reefs, trapezoidal reefs in three different layouts were selected for analysis at five different velocity gradients (0.1, 0.5, 1.0, 1.5, and 2.0 m/s). The effects of disposal spacing and layout on the flow field effect of trapezoidal artificial reefs at different flow velocities were simulated using Ansys Fluent. According to the findings: after simulation, flow velocity could indirectly reflect the distribution of upwelling and back eddy, the scale and strength of upwelling increased as flow velocity increased, and the back eddy showed no obvious variation with flow velocity. In transverse combination mode, both the scale and strength of the upwelling and back eddy were maximized when the reef spacing was 1.0 L; in longitudinal combination mode, upwelling and back eddy reached maximum scale and strength when the disposal spacing of the reefs was 1.5 L of a single reef. In 2020, flow mapping and fishery surveys were carried out in the engineering pilot area. The results showed that the number and species of fish populations with 1.5 L spacing in the vertical combination method were significantly higher than those in other forms, and the structure of the fish reef was stable without any flipping or sliding phenomenon. This study can provide a theoretical reference for the design and the actual deployment of artificial reefs to improve the ecological restoration of the water.

Transcriptomic analysis of the antioxidant responses and immunomodulatory effects of dietary melatonin in red swamp crayfish (Procambarus clarkii) - Yiming Li; Yucong Ye; Siwen Li; Jianbin Feng; Xingguo Liu; Xuan Che; Qichen Jiang; Xiaolong Chen (Fish & Shellfish Immunology, 2023)

Polystyrene nanoplastics decrease nutrient accumulation, disturb sex hormones, and inhibit reproductive development in juvenile Macrobrachium nipponense - Yiming Li; Yucong Ye; Na Rihan; Qichen Jiang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

Two genes related to apoptosis in the hepatopancreas of juvenile prawn, Macrobrachium nipponense: Molecular characterization and transcriptional response to nanoplastic exposure - Yiming Li; Xinglin Du; Wen Li; Qichen Jiang; Yucong Ye; Ying Yang; Xingguo Liu; Yunlong Zhao; Xuan Che (Science of The Total Environment, 2023)

Hydrodynamics of waste collection in a recirculating aquaculture tank with different numbers of inlet pipes - Jun Zhang; Zhihao Zhang; Xuan Che; Congcong Chen; Yang Gao; Ning Zhang; Dinala Maidaibieke; Xingyu Zhu; Chen Ziling (Aquacultural Engineering, 2023)

Responses of macrozoobenthos communities to changes in submerged macrophyte biomass in 19 temperate lakes in China - Hao Zhu; Shuiping Cheng; Xiaoke Zhang; Xingguo Liu; Xuan Che (Environmental Science and Pollution Research, 2022)

Correction to: Involvement of P2Y12 receptor of stellate ganglion in diabetic cardiovascular autonomic neuropathy - Jingjing Guo; Xuan Sheng; Yu Dan; Yurong Xu; Yuanruohan Zhang; Huihong Ji; Jiayue Wang; Zixi Xu; Hongyu Che; Guodong Li; Shangdong Liang; Guilin Li (Purinergic Signalling, 2021)

Involvement of P2Y12 receptor of stellate ganglion in diabetic cardiovascular autonomic neuropathy - Jingjing Guo; Xuan Sheng; Yu Dan; Yurong Xu; Yuanruohan Zhang; Huihong Ji; Jiayue Wang; Zixi Xu; Hongyu Che; Guodong Li; Shangdong Liang; Guilin Li (Purinergic Signalling, 2018)

Genome-wide DNA methylation analysis in jejunum of Sus scrofa with intrauterine growth restriction - Yue Hu; Liang Hu; Desheng Gong; Hanlin Lu; Yue Xuan; Ru Wang; De Wu; Daiwen Chen; Keying Zhang; Fei Gao; Lianqiang Che (Molecular Genetics and Genomics, 2018)

Greenhouse gas emissions and comprehensive greenhouse effect potential of Megalobrama amblycephala culture pond ecosystems in a 3-month growing season - Lin Zhu; Xuan Che; Huang Liu; Xingguo Liu; Chong Liu; Xiaolong Chen; Xu Shi (Aquaculture International, 2016)

Aspirin and nonsteroidal anti-inflammatory drugs after but not before diagnosis are associated with improved breast cancer survival: a meta-analysis - Xuan-zhang Huang; Peng Gao; Jing-xu Sun; Yong-xi Song; Cheng-che Tsai; Jing Liu; Xiao-wan Chen; Ping Chen; Hui-mian Xu; Zhen-ning Wang (Cancer Causes & Control, 2015)

The Chebyshev spectral element method using staggered predictor and corrector for elastic wave simulations - Cheng-Xuan Che; Xiu-Ming Wang; Wei-Jun Lin (Applied Geophysics, 2010)